CD8+ tumor‐infiltrating lymphocytes within the primary tumor of patients with synchronous de novo metastatic colorectal carcinoma do not track with survival. Issue 7 (17th July 2020) - Millen, Rosemary; Hendry, Shona; Narasimhan, Vignesh; Abbott, Rebecca; Croxford, Matthew; Gibbs, Peter; Tie, Jeanne; Wong, Hui‐Li; Jones, Ian; Kosmider, Suzanne; Byrne, David; Zalcberg, John; et al.
Abstract: Objectives: Tumor‐infiltrating lymphocytes (TIL), particularly CD8 + TILs in patients with colorectal cancer (CRC), are highly prognostic in the early‐disease stages (I‐II). In metastatic disease (stage IV; mCRC), their influence is less well defined. It has presumably failed to contain tumor cells to the primary site; however, is this evident? We explored the prognostic impact of TILs at the primary site in patients who presented de novo with mCRC. Methods: Treatment‐naïve patients (109) with mCRC were assessed for CD8 + TILs and PD‐L1 expression. Microsatellite instability (MSI) was evaluated by IHC for PMS2 and MSH6 proteins and/or by PCR using the Bethesda panel. Results: Microsatellite instability‐high tumors had significantly more CD8 + TILs, with no significant survival advantage observed between MSI‐H and microsatellite stable (MSS) tumors (12 vs 19 months, P  = 0.304). TIL density for all cases had no impact on OS (low: 20 vs high: 13 months, P  = 0.426), while PD‐L1 of 1% or higher was associated with reduced mean survival (9.6 vs 18.9 months; P  = 0.038). MSI‐H tumors and associated immune cells had higher PD‐L1 expression than in MSS cases. A positive correlation between PD‐L1 on immune cells and CD8+ve TILs was found. A subset of MSS tumors had relatively high TILs approximating that of MSI‐H tumors. Conclusion: In contrast to early‐stage CRC, the immune response in primary tumors of patients with de novo mCRC does not appear to influence survival. A subgroup of MSS tumors was identified with increased TILs/PD‐L1 comparable to MSI‐H tumors, traditionally not be considered for immune checkpoint blockade and perhaps should be. Abstract : Unlike early‐stage colorectal cancer (CRC), the immune response in primary tumors of patients with de novo mCRC does not appear to influence survival despite MSI‐H tumors having higher tumor infiltrating lymphocytes (TILs). This unique cohort of patients with synchronous mCRC by definition represents the breakdown of immune containment of the primary tumor. Despite this, we also identified a subgroup of MSS tumors with a high TILs comparable to MSI‐H tumors and this group traditionally would not be considered for immune checkpoint blockade, and perhaps should be.